Behind the shattered glass [large type] - Alexander, Tasha, 1969- (Alexander, Tasha, 1969- Lady Emily mystery., 2014)
When their neighbor, a young aristocrat, is murdered, Lady Emily Hargreave and her husband Colin examine the motives of those closest to him to catch a killer amidst dark secrets and forbidden passions.